Selective optogenetic stimulation of glutamatergic, but not GABAergic, vestibular nuclei neurons induces immediate and reversible postural imbalance in mice. (September 2021) - Montardy, Q.; Wei, M.; Liu, X.; Yi, T.; Zhou, Z.; Lai, J.; Zhao, B.; Besnard, S.; Tighilet, B.; Chabbert, C.; Wang, L.
Highlights: Vestibular nuclei were optogenetically stimulated, to asses for glutamate and GABA neurons functions in posturo-locomotor behaviors. Brief optogenetic activation of VNVGluT2+, but not VNGAD2+, induced immediate and strong postural deficit. Stimulation of VNVGluT2+ neurons provoked an imbalance with continuous effect on locomotion for a short period of time after stimulation. Stimulation are comparable to classical vestibular deafferentation models at their peak, setting it as a new model to study vestibular deficits. Abstract: Glutamatergic and GABAergic neurons represent the neural components of the medial vestibular nuclei. We assessed the functional role of glutamatergic and GABAergic neuronal pathways arising from the vestibular nuclei (VN) in the maintenance of gait and balance by optogenetically stimulating the VN in VGluT2-cre and GAD2-cre mice. We demonstrate that glutamatergic, but not GABAergic VN neuronal subpopulation is responsible for immediate and strong posturo-locomotor deficits, comparable to unilateral vestibular deafferentation models. During optogenetic stimulation, the support surface dramatically increased in VN VGluT2+ mice, and rapidly fell back to baseline after stimulation, whilst it remained unchanged during similar stimulation of VN GAD2+ mice. This effect persisted when vestibular tactilo kinesthesic plantar inputs were removed. Posturo-locomotor alterations evoked in VN VGluT2+ animals were still present immediately after stimulation, while they disappeared 1 h later. Overall, these results indicate a fundamental role for VN VGluT2+ neurons in balance and posturo-locomotor functions, but not for VN GAD2+ neurons, in this specific context. This new optogenetic approach will be useful to characterize the role of the different VN neuronal populations involved in vestibular physiology and pathophysiology.